2002
DOI: 10.51378/eca.v57i644.5617
|View full text |Cite
|
Sign up to set email alerts
|

Tercer informe anual del gobierno de Flores

Abstract: No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 57, No. 644, 2002: 583-588.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…PROCAMPO covers 95 percent of the cultivated area in Mexico that had been planted in corn, beans, sorghum and wheat (SAGAR, 1998); this represents approximately 14 million hectares and almost three million producers a year. Annual payments are over US$1 billion which is 60 percent of the budget of the Ministry of Agriculture (Fox 2003). PROCAMPO is particularly important in the ejido (land reform) sector where 84 percent of ejidatarios participated in PROCAMPO and received payments for, on average, 5.2 hectares (Cord and Wodon, 1999).…”
Section: A Procampomentioning
confidence: 99%
See 1 more Smart Citation
“…PROCAMPO covers 95 percent of the cultivated area in Mexico that had been planted in corn, beans, sorghum and wheat (SAGAR, 1998); this represents approximately 14 million hectares and almost three million producers a year. Annual payments are over US$1 billion which is 60 percent of the budget of the Ministry of Agriculture (Fox 2003). PROCAMPO is particularly important in the ejido (land reform) sector where 84 percent of ejidatarios participated in PROCAMPO and received payments for, on average, 5.2 hectares (Cord and Wodon, 1999).…”
Section: A Procampomentioning
confidence: 99%
“…In 2001 the Fox administration changed the name of the program to OPORTUNIDADES and expanded coverage to semi-urban and poor urban areas. The program budget reached US$1.9 billion in 2002, covering nearly 3 million rural households and over 1.2 million urban ones (Fox, 2003). Because PROGRESA conditions payment of transfers on school attendance and visits to health care facilities, it was expected and has been shown that the program had a significant impact on education attendance and health outcomes (Skoufias and McClafferty, 2001).…”
Section: B Progresamentioning
confidence: 99%